Pengembangan Media Video Pembelajaran Ilmu Pengetahuan Sosial pada Siswa Sekolah Dasar - Friendha Yuanta (Trapsila: Jurnal Pendidikan Dasar, 2019)
Development of instructional media for learning valid and effective video learning media as a learning resource for social studies learning in grade IV elementary school. The development of this instructional video media uses the ASSURE model which has 6 stages: (1) analysis of students, (2) determining learning objectives, (3) choosing methods, media and materials, (4) using media and materials, (5) encouraging participation students, (6) evaluation and improvement. The subject of the development of this instructional video media is Grade IV students of SDN Pakis V. The development of this video media is declared valid to be used in social studies learning in class IV. This is obtained from the results of the validation of media experts, material experts, individual students, small groups, large groups / classical. After testing the experts and testing the students then conducted trials aimed at learning effectiveness using this instructional video media. Test results obtained in the use of instructional video media show that students have succeeded in getting grades above the specified KKM. Thus it can be denied that this instructional video learning media is effective for use in the learning process. Keywords: media development, video learning, social studies.